Challenges of Remote/Flexible Teaching in Professional Technical and Technological Education in the Context of the COVID-19 (Research, Society and Development, 2022)
This article is the result of a systematic review on the challenges of Brazilian education in times of the COVID-19 pandemic and seeks to discuss remote/flexible teaching in Brazilian public schools, especially in the context of Vocational, Technical and Technological Education. The study proposes to discuss in the hybrid teaching perspective, pointed out by Bacich et al. (2015) and developed at the institutional level in the pandemic context during the process of readaptation and reorganization of schools in the use of digital platforms. For this, the choice was made by a qualitative research, through which we carried out bibliographic investigations, approaching the assumptions pointed out by Almeida; Dalben, 2020, which establishes the process of implementing flexible teaching adopted by Vocational, Technical and Technological Education, as well as Calejon & Brito, 2020 and Santana & Sales, which highlight the new methodologies and approaches used in the hybrid model and their importance in evaluation of pedagogical practices developed by education professionals during the Covid-19 pandemic. Among the results, we identified that Professional, Technical and Technological Education discussed the perspectives of the current moment and the return in the post-pandemic and developed didactic-pedagogical plans and actions that aimed to mitigate the impacts caused by COVID-19 to students.